Mohamad Samsulsairi builds Tako Engineer empire - Halizan, Mohmood (UMPSA, 2024)
GAMBANG, 24 January 2024 - Holistic, entrepreneurial and balanced graduates are one of the elements of the leap in the Malaysia Education Development Plan 2015-2025 (Higher Education).